2005
DOI: 10.1007/s00401-005-1057-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal intranuclear inclusions are ultrastructurally and immunologically distinct from cytoplasmic inclusions of neuronal intermediate filament inclusion disease

Abstract: Abnormal neuronal cytoplasmic inclusions (NCIs) containing aggregates of α-internexin and the neurofilament (NF) subunits, NF-H, NF-M, and NF-L, are the signature lesions of neuronal intermediate filament (IF) inclusion disease (NIFID). The disease has a clinically heterogeneous phenotype, including fronto-temporal dementia, pyramidal and extrapyramidal signs presenting at a young age. NCIs are variably ubiquitinated and about half of cases also have neuronal intranuclear inclusions (NIIs), which are also ubiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 35 publications
(91 reference statements)
8
35
1
Order By: Relevance
“…Some of these filaments were broader in the nuclear compartment than any TDP-43-positive filaments observed in the NCIs or DNs. Interestingly, we showed previously that the filaments of NIIs of neuronal intermediate filament inclusion disease (NIFID) were broader than those of the NCIs (20 nm compared with 10 nm; Mosaheb et al 2005). Whilst the granular component of the NII of FTLD with TDP-43 proteinopathy was relatively minor, this granular component predominated within most of the mature, swollen DNs and contained frequent TDP-43 epitopes.…”
Section: Discussionmentioning
confidence: 96%
“…Some of these filaments were broader in the nuclear compartment than any TDP-43-positive filaments observed in the NCIs or DNs. Interestingly, we showed previously that the filaments of NIIs of neuronal intermediate filament inclusion disease (NIFID) were broader than those of the NCIs (20 nm compared with 10 nm; Mosaheb et al 2005). Whilst the granular component of the NII of FTLD with TDP-43 proteinopathy was relatively minor, this granular component predominated within most of the mature, swollen DNs and contained frequent TDP-43 epitopes.…”
Section: Discussionmentioning
confidence: 96%
“…Chronic degenerative changes may affect a variety of cortical and subcortical regions, with the frontal and temporal lobes and caudate nucleus most consistently and severely involved. Several different types of neuronal cytoplasmic and intranuclear inclusions (NCI and NII, respectively) have been described, that vary in morphology, histochemical staining, immunoreactivity, ultrastructure and anatomical distribution [8, 29, 36]. By definition, these inclusions show no immunoreactivity for tau, α-synuclein or TDP-43 but at least some are immunoreactive for IFs.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical studies of post mortem brain tissue have failed to demonstrate any abnormal molecular modification of IFs in NIFID [11, 29] and no pathogenic variants of the corresponding genes have been identified [28]. More importantly, several published reports of NIFID have indicated that only a proportion of the inclusions are IF-ir [6, 18, 24, 36, 41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially termed "neurofilament inclusion disease," this condition was renamed "neuronal IF inclusion disease" when ␣-internexin was discovered in the pathological inclusions, underscoring the prevailing view that ␣-internexin is not a component of the neurofilament (Cairns et al, 2004a,b,c;Momeni et al, 2005;Mosaheb et al, 2005). ␣-Internexin is also implicated in tropical spastic paraparesis/human T-cell leukemia virus type 1-associated myelopathy (Reddy et al, 1998), a degenerative CNS disorder in which neurofilaments accumulate in giant axonal spheroids (Wu et al, 1993;Liberski et al, 1994;Liberski et al, 1999).…”
Section: Introductionmentioning
confidence: 99%